Les Compléments Alimentaires en Officine - LAKHAL , Amira; LAOUAR , Meriem; KOUROUGHLI , Roumaissa; ZEGGAR , M (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine., 2023)
Dietary supplements, are concentrated sources of nutrients, that is, vitamins and mineral salts, nutritional or physiological substances, or plants and plant preparations that are intended to compensate for a person’s lack of a regular diet. Dietary supplements include substances for different uses: gynaecological, weight gain, stress relief, energy stimulation, weight loss, anti-aging and strength training. It has been shown that excessive and unhealthy use of Dietary supplements can cause several damages such as cardiovascular, digestive and neurological disorders, liver and kidney damage, and even some cancers. Advertising and labelling of Dietary supplements must not state that these products have properties that prevent, cure or treat any disease.
لمكملات الغذائية هي مصادر مركزة للعناصر الغذائية، أي الفيتامينات والأملاح المعدنية، والمواد الغذائية أو الفزيولوجية، أو النباتات والمستحضرات النباتية التي تهدف إلى تعويض افتقار الشخص إلى نظام غذائي منتظم . تشمل مواد لاستخدامات مختلفة: أمراض النساء وزيادة الوزن وتخفيف الإجهاد وتحفيز الطاقة وفقدان الوزن ومكافحة الشيخوخة وتدريب القوة. لقد ثبت أن الاستخدام المفرط وغير الصحي لـلمكملات الغذائية يمكن أن يسبب العديد من الأضرار مثل اضطرابات القلب والأوعية الدموية والجهاز الهضمي والعصبي وتلف الكبد والكلى وحتى بعض أنواع السرطان. لذا يجب ألا ينص الإشهار على أن هذه المنتجات لها خصائص تمنع أو تعالج أو أي مرض
Keywords: Les compléments alimentaires; pallier les carences; la publicité; l'étiquetage.